Computer simulation a foundational approach using Python - Osais, Yahya E. (Chapman & Hall/CRC computer & information science series, 2018)
Computer simulation is an effective and popular universal tool that can be applied to almost all disciplines. Requiring only basic knowledge of programming, mathematics, and probability theory, Computer Simulation: A Foundational Approach Using Python takes a hands-on approach to programming to introduce the fundamentals of computer simulation. The book will be of great interest to senior undergraduate and starting graduate students in the fields of computer science and engineering and industrial engineering.